Mechanism for control of legislative power in the 2013 constitution of Vietnam - Trinh, Thang Xuan (Đại học Quốc gia Hà Nội, 2020)
Legislative power is one of the most important powers of the state apparatus, and is aimed to establish the state’s legal system. Therefore, it is necessary to have a mechanism to control the legislative power of the National Assembly so as to ensure that this type of power is properly implemented, in order to create a quality legal system that effectively serves the state in management activities, and limit the abuse of power and the arbitrary issuance of law. The Constitution, as the supreme law, contains fundamental provisions on mechanisms for state power control, including the control of the legislative power of the National Assembly. Therefore, there are several issues that will be addressed in this study, including: What is the objective necessity of the legislative control mechanism of the National Assembly? What is the current status of the National Assembly’s control of legislative power in the 2013 Constitution and the implementation of this power ful control mechanism in practice? What is the orientation of the ongoing improvement of the current legislative control mechanism of the National Assembly of Vietnam? On that basis, this paper will focus on clarifying these research issues.